Cierpienie a wola Boża u świętej Faustyny Kowalskiej - Halina Szyller (Wrocławski Przegląd Teologiczny)
It is hard for an human being to accept his suffering as a part of a process of spiritual growth. However St. Faustyna proves that identification and union with Jesus through the suffering is beneficial to save the lost souls. All her work on the internal life had been based on the union of her own will with God’s will, and her obedience without her logic and opinions. The Saint declares that God’s will is the one and only object of her love. When she stayed at the hospital for three months, suffering from tuberculosis, she realized that this is the time not only for the treatment, but intensive work to save sinners. In order to be obedient to Jesus, and to identify with His sacrifice, she unites with Christ on the Cross. What was important in this union is the suffering and love combined together. She clearly gets to experience all kinds of suffering in her new role. She agrees to her new identity with bravery and devotion: My name is “Sacrifice”. When her sacrifice becomes complete, she declares “My name is the Sacramental Bread “, hidden sacrifice.